The prediction of upper gastrointestinal bleeding in nonsteroidal anti-inflammatory drug users - Mayuree Tangkiatkumjai (Chulalongkorn University, 2009)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 2001